Wednesday
March 22, 2017

Post a New Question

Posted by on Monday, October 15, 2012 at 11:23am.

deriv.
h(t)=(tˆ4-1)ˆ3(tˆ3+1)ˆ4

  • Calc - , Monday, October 15, 2012 at 11:42am

    product rule and chain rule:

    h = uv
    h' = u'v + uv'

    if u=w^n, u' = n w^(n-1) w'

    so, whatcha got?

  • Calc - , Tuesday, October 16, 2012 at 5:15pm

    (3t^4-3)^2(4t^6+4t^3)^4+(t^4-1)^3(12t^4+12t)^3
    but i'm not sure if this is a simple as it gets.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question